1998
DOI: 10.1016/s0014-5793(97)01529-9
|View full text |Cite
|
Sign up to set email alerts
|

Homodimerization of IL‐2 receptor β chain is necessary and sufficient to activate Jak2 and dowstream signaling pathways

Abstract: Cytokine receptor signaling involves the Jak/Stat pathways. Heterotrimeric IL-2R (K K, L L, Q Q chains) activates Jak1 and Jak3, whereas homodimeric PRLR activates Jak2. The requirements directing such specificity of Jak activation are unknown. We show that chimeric receptors containing the intracellular domain of IL-2RL L chain fused to the extracellular domain of either EPOR or Kit, a non-cytokine receptor, activate Jak2. This observation provides evidence that IL-2RL L intrinsically possesses the ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…When transfected alone, IL-2Rβ forms a homodimer able to bind IL-2 [51]. Complexes of IL-2Rβ, formed by the intra-cellular domain of IL-2Rβ fused to the extracellular domain of c-kit, have been shown to activate the Jak2 pathway [52] whereas IL-2 receptor signalling through the conventional α/β/γ complex leads to phosphorylation of Jak1 and 3. Similar experiments have not been performed with IL-15, which is synthesized by decidual cells and thus more likely than IL-2 to stimulate the trophoblast IL-2Rβ in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…When transfected alone, IL-2Rβ forms a homodimer able to bind IL-2 [51]. Complexes of IL-2Rβ, formed by the intra-cellular domain of IL-2Rβ fused to the extracellular domain of c-kit, have been shown to activate the Jak2 pathway [52] whereas IL-2 receptor signalling through the conventional α/β/γ complex leads to phosphorylation of Jak1 and 3. Similar experiments have not been performed with IL-15, which is synthesized by decidual cells and thus more likely than IL-2 to stimulate the trophoblast IL-2Rβ in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Previous studies suggested that ␥c-related receptors including IL-2R␤ chain and IL-4R␣ chain could activate janus-activated kinases (JAKs) to some extent in the presence of the extracellular domain of ␥c, independent of the cytoplasmic domain of ␥c. 24,25 Thus, in order to block the signaling through ␥c-related cytokine receptors more completely, we made NOD/SCID mice harboring complete null mutation of ␥c 16 (the NOD/SCID/IL2r␥ null strain). By using NOD/SCID/IL2r␥ null newborns, we successfully reconstituted myeloerythroid as well as lymphoid maturation by injecting human CB or highly-enriched CB HSCs at a high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…he pleiotropic actions of the somatolactogenic hormone prolactin (PRL) are mediated by signaling through the prolactin receptor, a member of the type I family of cytokine receptors (1)(2)(3). Upon ligand binding and dimerization of the receptor, several signaling cascades are activated, including Ras-Raf, Fyn-Vav and Jak2-Stat5 (4-7).…”
mentioning
confidence: 99%